The Use of Electrophilic Cyclization for the Preparation of Condensed Heterocycles - Slivka, Mikhailo; Onysko, Mikhailo (Synthesis, 2021)
Condensed heterocycles are well-known for their excellent biological effects and they are undeniably important compounds in organic chemistry. Electrophilic cyclization reactions are widely used for the synthesis of mono-heterocyclic compounds. This review highlights the utility of electrophilic cyclization reactions as an effective generic tool for the synthesis of various condensed heterocycles containing functional groups that are able to undergo further chemical transformations, such as nucleophilic substitution, elimination, re-cyclization, cleavage, etc. This review describes the reactions of unsaturated derivatives of different heterocycles with various electrophilic agents (halogens, arylsulfanyl chlorides, mineral acids) resulting in annulation of an additional partially saturated heterocycle. The electrophilic reaction conditions, plausible mechanisms and the use of such transformations in organic synthesis are also discussed. The review mainly focuses on research published since 2002 in order to establish the current state of the art in this area. 1 Introduction2 Electrophilic Cyclization Pathways Involving a Nitrogen Nucleophilic Center3 Electrophilic Cyclization Pathways Involving a Chalcogen Nucleophilic Center3.1 Sulfur Centers3.2 Oxygen Centers3.3 Selenium Centers4 Strategies and Mechanisms5 Conclusion
Keywords: electrophilic cyclization; condensed heterocycles; heteroaryl alkenes; heteroaryl alkynes; bromine; iodine; arylsulfanyl chlorides